General Household Emergency Preparedness: A Comparison Between Veterans and Nonveterans - Der-Martirosian, Claudia (Prehosp Disaster Med, 2014)
BACKGROUND: Despite federal and local efforts to educate the public to prepare for major emergencies, many US households remain unprepared for such occurrences. United States Armed Forces veterans are at particular risk during public health emergencies as they are more likely than the general population to have multiple health conditions. METHODS: This study compares general levels of household emergency preparedness between veterans and nonveterans by focusing on seven surrogate measures of household emergency preparedness (a 3-day supply of food, water, and prescription medications, a battery-operated radio and flashlight, a written evacuation plan, and an expressed willingness to leave the community during a mandatory evacuation). This study used data from the 2006 through 2010 Behavioral Risk Factor Surveillance System (BRFSS), a state representative, random sample of adults aged 18 and older living in 14 states. RESULTS: The majority of veteran and nonveteran households had a 3-day supply of food (88% vs 82%, respectively) and prescription medications (95% vs 89%, respectively), access to a working, battery-operated radio (82% vs 77%, respectively) and flashlight (97% vs 95%, respectively), and were willing to leave the community during a mandatory evacuation (91% vs 96%, respectively). These populations were far less likely to have a 3-day supply of water (61% vs 52%, respectively) and a written evacuation plan (24% vs 21%, respectively). After adjusting for various sociodemographic covariates, general health status, and disability status, households with veterans were significantly more likely than households without veterans to have 3-day supplies of food, water, and prescription medications, and a written evacuation plan; less likely to indicate that they would leave their community during a mandatory evacuation; and equally likely to have a working, battery-operated radio and fiashlight. CONCLUSION: These findings suggest that veteran households appear to be better prepared for emergencies than do nonveteran households, although the lower expressed likelihood of veterans households to evacuate when ordered to do so may place them at a somewhat greater risk of harm during such events. Further research should examine household preparedness among other vulnerable groups including subgroups of veteran populations and the reasons why their preparedness may differ from the general population.